Screening of Genetic Risk among Relatives and the General Public: Exploring the Spectrum of the Psychosis Prodrome - Razali, Salleh Mohd; Abidin, Zarina Zainan; Othman, Zaharuddin; Yassin, Mohd Azhar Mohd (Japan International Cultural Exchange Foundation, 2013)
Objective: A large percentage of subjects with self-reported psychotic-like experiences (PLE) are found in the community and their status is unclear. The aim of the study is to detect the prevalence of non-affective psychosis and those vfith PLE among the relatives of patients with schizophrenia and the general public. Materials and methods: This was a two-stage procedure involving the first and second degree relatives of patients with schizophrenia and the general public. In the initial stage, the subjects were screened using a Screening Questionnaire (SQ). The positive subjects proceeded to the second stage and were assessed using the Comprehensive Assessment of At-Risk Mental State (CAARMS), the Global Assessment of Function (GAF), Hamilton Depression Rating Scale (HDRS) and Hamilton Anxiety Rating Scale (HARS). Results: A total of 660 subjects equally divided between the two groups formed a final sample. In the first stage, 170 (26%) subjects had positive scores on the SQ which was significantly higher in the general public. In the second stage, 34 (20%) cases were found to be positive, with a higher proportion among the relatives at genetic risk. The numbers of subjects with subthreshold of attenuated psychotic symptoms (STAPS) (27%) and STAPS with affective symptoms (STAPSAS) (32%) detected was higher than those at Ultra High Risk (UHR) (23%) and non-affective psychosis (18%). Although no significant difference in the number of specific cases was detected between the general public and relatives at genetic risk, the proportion of relatives at genetic risk steadily increased as the illness progressed to full blown psychosis. Conclusions: Clinical assessment or re-interview following a self-report questionnaire is mandatory to detect individuals with psychotic disorders. The prevalence of subjects with elementary PLE (sub-threshold of APS) was higher than subjects with established psychotic symptoms such as UHR individuals. The prevalence of depression was high in pre-psychotic states before the psychotic symptoms became prominence. The contribution of genetic factors was more prominent as the illness progresses to frank psychosis.